2010
DOI: 10.1007/s00421-010-1554-z
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac function and arteriovenous oxygen difference during exercise in obese adults

Abstract: The purpose of this study was to assess cardiac function and arteriovenous oxygen difference (a-vO(2) difference) at rest and during exercise in young, normal-weight (n = 20), and obese (n = 12) men and women who were matched for age and fitness level. Participants were assessed for body composition, peak oxygen consumption (VO(2peak)), and cardiac variables (thoracic bioimpedance)-cardiac index (CI), cardiac output (Q), stroke volume (SV), heart rate (HR), and ejection fraction (EF)-at rest and during cycling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
1
10
2
Order By: Relevance
“…This finding, while not significant, is in agreement with results reported by Kanegusuku et al (2016), which revealed lower SBP values in PD patients compared to CON at sub-maximal and peak intensities. During exercise, changes in SVI and CI were comparable to those of other studies using treadmills and cycling (Mile et al 1984, Thadani and Parker 1978, Vella et al 2011. It should be noted, however, that these studies included predominately younger subjects.…”
Section: Discussionsupporting
confidence: 79%
“…This finding, while not significant, is in agreement with results reported by Kanegusuku et al (2016), which revealed lower SBP values in PD patients compared to CON at sub-maximal and peak intensities. During exercise, changes in SVI and CI were comparable to those of other studies using treadmills and cycling (Mile et al 1984, Thadani and Parker 1978, Vella et al 2011. It should be noted, however, that these studies included predominately younger subjects.…”
Section: Discussionsupporting
confidence: 79%
“…The C(a‐v)O 2 between our groups (OB, LF‐OB, HF‐OB and AMHC) was not different which is in disagreement with previous studies (Vella et al. , ; Fournier et al. ).…”
Section: Discussioncontrasting
confidence: 75%
“…) but is inconsistent with results from two other studies (Vella et al. , ). The C(a‐v)O 2 between our groups (OB, LF‐OB, HF‐OB and AMHC) was not different which is in disagreement with previous studies (Vella et al.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Aerobic exercise increases blood flow and provides better delivery of nutrients and oxygen, allowing for a better overall growth rate of the fetus in later pregnancy 49 . The improvement of the VO 2max may induce an increase in blood supply to tissues leading to high diffusion of oxygen, improving the ability to extract oxygen from the blood into all tissues 50 .…”
Section: Discussionmentioning
confidence: 99%